Highly Efficient Phosphorescent Blue-Emitting [3+2+1] Coordinated Iridium (III) Complex for OLED Application - Liu, Zijian; Zhang, Si-Wei; Zhang, Meng; Wu, Chengcheng; Li, Wansi; Wu, Yuan; Yang, Chen; Kang, Feiyu; Meng, Hong; Wei, Guodan (Frontiers in Chemistry, 2021)
Cyclometalated iridium (III) complexes are indispensable in the field of phosphorescent organic light-emitting diodes (PhOLEDs), while the improvement of blue iridium (III) complexes is as yet limited and challenging. More diversified blue emitters are needed to break through the bottleneck of the industry. Hence, a novel [3+2+1] coordinated iridium (III) complex (noted as Ir-dfpMepy-CN) bearing tridentate bis-N-heterocyclic carbene (NHC) chelate (2,6-bisimidazolylidene benzene), bidentate chelates 2-(2,4-difluorophenyl)-4-methylpyridine (dfpMepy), and monodentate ligand (-CN) has been designed and synthesized. The tridentate bis-NHC ligand enhances molecular stability by forming strong bonds with the center iridium atom. The electron-withdrawing groups in the bidentate ligand (dfpMepy) and monodentate ligand (-CN) ameliorate the stability of the HOMO levels. Ir-dfpMepy-CN shows photoluminescence peaks of 440 and 466 nm with a high quantum efficiency of 84 ± 5 %. Additionally, the HATCN (10 nm)/TCTA (10 nm)/10 wt% Ir-dfpMepy-CN in DPEPO (10 nm)/TmPyPB (40 nm)/Liq(2.5 nm) OLED device employed the complex shows a CIE coordinate of (0.16, 0.17), reaching a deeper blue emission. The high quantum efficiency is attributed to the large proportion of metal involved transition and rapid metal to ligand charge transfer (MLCT) transition of 0.6 - 2.1 ps, which enhances the contribution of the metal to ligand charge transfer in the triplet iridium (III) complex configuration, which has opened a new window to develop new blue emitters and dopant alternatives for future efficient blue PhOLEDs.